Monitoring Vaginal Electrical Impedance in Bangladeshi Water Buffaloes During Postpartum Period - Juyena, Nasrin Sultana; Hassan, Mahmudul; Mollah, Habibur Rahman; Rabidas, Shushanto Kumar (Journal of Buffalo Science, 2015)
The achievement of early cyclicity and pregnancy after calving are of vital importance for sustainable buffalo farms, for which proper detection of oestrus and correct time of AI are necessary. Vaginal electrical impedance (VEI) observation using heat detector was used to identify estrus in buffalo cows during post-partum period. In the first group, 12 buffalo cows with post-partum>300 days were synchronized with OVSYNCH protocol and VEI was recorded at different stages of synchronization protocol. VEI values decreased significantly (P < 0.01) during second administration of GnRH in both pregnant and non-pregnant buffalo cows and it was indicative for the presence of oestrus. Higher VEI values were obvserved at second administration of GnRH and AI in non-pregnant group than the pregnant group. In second group, 8 buffalo cows with a post-partum period 40 to 96 days were used to record VEI daily. Lower VEI values (260-350Ω) were observed during oestrus and then started to increase at higher level after oestrus. The day difference between two successive lower/higher values of “VEI waves” ranged from 17-25 days, which might indicate the oestrous cycle in buffalo cows. Moreover, physical signs such as colour of vulva, mucus were less intensive in buffalo cows of second experiment. The study suggests that the measurement of vaginal impedance could serve as an indicator of the oestrus in buffalo cows and daily impedance measurements are necessary to confirm the stages of the estrous cycle.